Transformative climate adaptation in the United States: Trends and prospects - Shi, Linda; Moser, Susanne (Science (American Association for the Advancement of Science), 2021)
Successfully responding to the impacts of climate change will be a challenge for many communities, especially cities. Considering the situation in the United States, Shi and Moser examine how stakeholders can help to build urban resilience even in the absence of federal leadership. They discuss how local and state governments, private industry, and civil society can engage to adapt to the extreme weather events and other consequences of changing climate that are expected in the future. Preparing for these looming issues requires coherent, cohesive, and collective responses across all scales and sectors of society. Science , abc8054, this issue p. eabc8054 A Review highlights the many ways to help build greater urban resilience to climate change. As climate change intensifies, civil society is increasingly calling for transformative adaptation that redresses drivers of climate vulnerability. We review trends in how US federal government, private industry, and civil society are planning for climate adaptation. We find growing divergence in their approaches and impacts. This incoherence increases maladaptive investment in climate-blind infrastructure, justice-blind reforms in financial and professional sectors, and greater societal vulnerability to climate impacts. If these actors were to proactively and deliberatively engage in transformative adaptation, they would need to address the material, relational, and normative factors that hold current systems in place. Drawing on a review of transformation and collective impact literatures, we conclude with directions for research and policy engagement to support more transformative adaptation moving forward.